Adult educators as border crossers: Using transformative pedagogy to inform classroom practice - Andre P. Grace (Adult Education Research Conference, 1996)
This paper presents an understanding of transformative pedagogy that is sensitive to the social, cultural, and historical construction of identity—difference within classrooms as political and multicentric spaces and places. It relates that this border pedagogy emphasizes the inclusion of Others and values instrumental, social and cultural forms of adult education in developing transformative classroom practices. It considers themes, challenges, and risks impacting this development.